2021
DOI: 10.3390/jcm10132925
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of Mesenchymal Stromal Cells after Administration in Animal Models and Humans: A Systematic Review

Abstract: Mesenchymal Stromal Cells (MSCs) are of great interest in cellular therapy. Different routes of administration of MSCs have been described both in pre-clinical and clinical reports. Knowledge about the fate of the administered cells is critical for developing MSC-based therapies. The aim of this review is to describe how MSCs are distributed after injection, using different administration routes in animal models and humans. A literature search was performed in order to consider how MSCs distribute after intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 140 publications
2
51
1
Order By: Relevance
“…NCT05054803). With respect to biodistribution, our results are in line with studies performed by other authors showing a rapid clearance of cells after injection and no presence of cells (locally or systemically) at mid/long term after intrathecal administration [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…NCT05054803). With respect to biodistribution, our results are in line with studies performed by other authors showing a rapid clearance of cells after injection and no presence of cells (locally or systemically) at mid/long term after intrathecal administration [36,37].…”
Section: Discussionsupporting
confidence: 92%
“…The following comprehensive and interesting reviews are highly recommended. [166][167][168] To date, 1426 registered clinical trials spanning different trial phases have used MSCs for therapeutic purposes, which is four times the number reported in 2013. 169,170 As supported by a large body of preclinical studies and advancements in conducting clinical trials, MSCs have been proven to be effective in the treatment of numerous diseases, including nervous system and brain disorders, pulmonary diseases, 171 cardiovascular conditions, 172 wound healing, etc.…”
Section: An Overview Of Msc Tissue Origins and Therapeutic Potentialmentioning
confidence: 99%
“… 61 In a systematic review by Sanchez-Diaz and their colleagues in 2021, ICV injection of MSC was detected at 1-3 weeks after injection and then, decreased time-dependently. 62 Another study showed that MSCs can be detected in the brain up to 7 weeks after ICV injection. 63 The efficacy of MSC distribution in the brain may rely on the distance between injected site and brain, and the number of injected MSCs, hence, intrathecal injection at L4 and L5 levels may have a lower effect on the brain in this study.…”
Section: Discussionmentioning
confidence: 99%